Síntese e caracterização estrutural de novos compostos de índio (II) e índio(III) - Andrade, Fabiano Molinos de (2008)
This work presents the synthesis and crystallographical study of indium organometallic compounds series in II and III oxidation states. Br2In(diox)2CH2Br and tetrahedral indium cluster, In4R4 [R = C(SiMe3)3], were adopted as starting materials of this work. We have made two different systematic studies: (a) reaction of Br2In(diox)2CH2Br with dialkylselenides R1SeR2 (R1 = CH3, R2 = CH2Ph; R1 = C2H5, R2 = CH2Ph; R1 = R2 = CH2Ph) and (b) reaction between the tetrahedral indium cluster and different chalcogenide donor ligands, such as PhEEPh (E = S, Se and Te), ArTeTeAr (Ar = CH3C6H4) and PhEBr (E = Se and Te), and haloforms as well, CHX3 (X = Cl, Br and I). The haloforms were applied as mild halogen donors. Br2In(diox)2CH2Br is obtained by the direct reaction between InBr and CH2Br2 in 1,4-dioxane. The Br3InCH2Se(CH3)CH2Ph (1), Br3InCH2Se(C2H5)CH2Ph (2) and Br3InCH2Se(CH2Ph)2 (3) derivatives are obtained by the reaction between Br2In(diox)2CH2Br and their own dialkylselenides. Tetrahedral indium cluster is obtained by the reaction between InBr and C(SiMe3)3·2THF in equivalent amounts. The new organoindium subhalides, R2In2Cl2 (4), R2In2Br2 (5), R2In2I2 (6), and the new indium(III) dimeric compounds as well, [RIn(SPh)2]2 (7), [RIn(SePh)2]2 (8), [RIn(TePh)2]2 (9) and [RIn(ArPh)2]2 (10), [RIn(Br)SePh]2 (11), [RIn(Br)TePh]2 (12), were obtained by the direct reaction of tetrahedral indium cluster and their respective halide or chalcogenide donors.